Fiscal Equalisation: Principles and an Application to the European Union - Bernd Hayo; Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2003)
The paper derives a normative model for partial fiscal equalisation based on a number of axioms and allows for the existence of a specific fiscal need in the jurisdictions. The theoretical model is then empirically tested for the case of the European Union using data from 1986-97. It is found that most restrictions of the model appear to hold, in particular, relatively richer countries contribute more and those with greater fiscal needs, approximated by the importance of the agricultural sector, pay less. However, in the EU, an adjustment of net payments to changes in the actual importance of the spe-cific fiscal need for a country is lacking
Keywords: 330